Future climate or land use? Attribution of changes in surface runoff in a typical Sahelian landscape - Yonaba, Roland; Mounirou, Lawani Adjadi; Tazen, Fowé; Koïta, Mahamadou; Biaou, Angelbert Chabi; Zouré, Cheick Oumar; Queloz, Pierre; Karambiri, Harouna; Yacouba, Hamma (Comptes Rendus. Géoscience, 2023)
In this study, the Soil and Water Assessment Tool (SWAT) model is used to assess changes in surface runoff between the baseline (1995–2014) and future (2031–2050) periods in the Tougou watershed $(37~km^{2})$ in Burkina Faso. The study uses a combination of land use maps (for current and future periods) and a bias-corrected ensemble of 9 CMIP6 climate models, under two warming scenarios. An increase in rainfall (13.7% to 18.8%) is projected, which is the major contributor to the increase in surface runoff (24.2% to 34.3%). The land use change narrative (i.e. conversion of bare areas to croplands) is expected to decrease in surface runoff, albeit minor in comparison to the effect of future climate change. Similar findings are observed for annual maximum surface runoff. This study sheds light on the need to consider simultaneously future climate and land use in framing water management policies.